Polio eradication in Nigeria: evaluation of the quality of acute flaccid paralysis surveillance documentation in Bauchi state, 2016 - Adamu Ibrahim Ningi; Faisal Shuaib; Luka Mangveep Ibrahim; Jalal-Eddeen Abubakar Saleh; Khalid Abdelrahim; Isah Mohammed Bello; Bashir Abba; Ticha Jonhson Muluh; Fiona Braka; Sisay G. Tegegne; Abdullahi Wallah; Charles Korir; et al. (BMC, 2018)
Abstract Background Nigeria is the only country in Africa that is yet to be certified as polio free. Surveillance for acute flaccid paralysis (AFP) is the foundation of the polio eradication initiative since it provides information to alert both health managers and clinician that timely actions should be initiated to interrupt transmission of the polio virus. The strategy also provides evidence for the absence of wild poliovirus. This evaluation was performed to assess key quality indicators defined by the polio eradication program and thus to identify gaps to allow planning for corrective measures to achieve a polio-free situation in Bauchi state and in Nigeria at large. We conducted a cross-sectional descriptive study which involved a desk review of documents to authenticate the correctness and completeness of data, and a review of documented evidence for the quality of AFP surveillance. We interviewed Local Government Authority (LGA) surveillance officers and clinicians from focal and non-focal sites, along with caregivers of children with AFP and community leaders. The data were entered and analyzed in a Microsoft Excel spreadsheet. Methods We conducted a cross-sectional study of the AFP surveillance and documentation in eighteen of the twenty Local Government Areas (LGAs) of Bauchi State. We assessed the knowledge of the clinician at focal and non-focal sites on case definition of AFP, the number and method of stool specimen collection to investigate a case and types of training received for AFP surveillance. We verified AFP case investigations for the last three years: The caregivers (mothers) were interviewed to authenticate the reported information of AFP cases, the method used for stool specimen collection and feedbacks. Community leaders' knowledge on AFP surveillance was also assessed. Data was entered and analyzed in excel spread sheet. Results Of the 18 LGA Disease Surveillance and Notification Officers (DSNOs), only 2 (11%) and 5 (28%) had reports of polio outbreak investigations and supervisory visits at the lower levels, respectively. Furthermore, only 6 (33%) and 7 (39%) of the DSNOs had minutes of meetings and surveillance work plans, respectively. Of the 31 AFP cases investigated, only 39, 26, 23, and 23% had correct and complete information for the birth day, birth month, date of onset of paralysis, and date of investigation, respectively. Seventy-one percent of the clinicians at the AFP focal sites knew the correct definition for AFP compared with only 30% at the non-focal sites. Of the 38 caregivers (mothers), 16 (42%) did not remember the day or month the AFP investigation was conducted. However, 95% gave a correct number of stool samples collected and 40% mentioned that the samples were collected 24 h apart. Feedback was not given to 26 (68%) of the caregivers. The majority (79%) of the community leaders knew how to recognize a case of AFP and knew that the stool was the specimen required for the investigation, but 21% did not know to whom they should report a case of AFP in their community. Conclusion This study revealed a gap in the quality indicators for polio eradication in the state, especially regarding knowledge and documentation for AFP surveillance at the operational level. Regular training of the DSNOs and focal persons, regular sensitization of clinicians, community education, supplies of reporting tools, and ensuring their judicious use will improve AFP surveillance in the state.